2012
DOI: 10.4018/jdet.2012070104
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Predictive Relationship Between Online Social Presence and ONLE Interaction

Abstract: Open Network Learning Environments (ONLE) are oniine networks that afford learners the opportunity to participate in creative content endeavors, personalized identity projections, networked mechanism management, and effective collaborative community integration by appiying Web 2.0 tools in open environments. It supports social interaction by integrating User-Generated Content, Participatory Web, digital identities, sociai and networking iinkages, and collaborative learning community to ailow iearners manage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, Baker (2004) points out the immediate proximity of the teacher or the ability to respond quickly to the students, while Borup, West and Graham (2012) claim that an explicit teacher role is especially important for the students to experience social presence in the use of video lectures. Several studies have suggested a set of factors that are needed to establish social presence in a digital learning environment (Chih-Hsiung, Cherng-Jyh, Blocher, & Junn-Yih, 2012;Dow, 2008;Sherblom, 2010;Sung & Mayer, 2012). These studies focus first and foremost on mechanisms to improve the students' communication, activity, productivity and fulfilment of studies in a digital educational setting.…”
Section: Social Presencementioning
confidence: 99%
“…Moreover, Baker (2004) points out the immediate proximity of the teacher or the ability to respond quickly to the students, while Borup, West and Graham (2012) claim that an explicit teacher role is especially important for the students to experience social presence in the use of video lectures. Several studies have suggested a set of factors that are needed to establish social presence in a digital learning environment (Chih-Hsiung, Cherng-Jyh, Blocher, & Junn-Yih, 2012;Dow, 2008;Sherblom, 2010;Sung & Mayer, 2012). These studies focus first and foremost on mechanisms to improve the students' communication, activity, productivity and fulfilment of studies in a digital educational setting.…”
Section: Social Presencementioning
confidence: 99%